Religious Attendance and Biological Risk: A National Longitudinal Study of Older Adults - Suh, Hyungjun (Journal of religion and health, 2019)
Although several studies suggest that religious involvement is associated with healthier biological functioning in later life, most of this work is cross-sectional. We extend previous research by employing a longitudinal design. Our analysis of Health and Retirement Study (2006/2010) data suggests that older adults who attended religious services weekly or more in 2006 tend to exhibit fewer high-risk biomarkers in 2010 and greater reductions in allostatic load over the 4-year study period than respondents who attended yearly or not at all. These patterns persisted with adjustments for baseline allostatic load and a range of background variables.